Epistemological Obstacles in Solving PISA Adapted Problems on System of Linear Equations In Two Variables - Ningrum, Yunia Jumita; Dasari, Dadan; Prabawanto, Sufyani (Universitas Muhammadiyah Mataram, 2025)
This study aims to identify and analyze the epistemological obstacles encountered by junior high school students when solving PISA-based mathematical literacy problems on the topic of System of Linear Equations in Two Variables (SLETV), viewed from the perspective of PISA competency levels. The research seeks to contribute to the development of more effective mathematics instruction. This study is deemed essential because epistemological obstacles can hinder students' ability to apply mathematical concepts in real-world contexts an ability that is central to international assessments such as PISA. A qualitative approach was employed through Didactical Design Research (DDR), involving 23 ninth-grade students. Data were collected through a written test consisting of a mathematical literacy problem adapted from PISA items, and supported by interviews and classroom observations. The data were analyzed using qualitative descriptive methods, focusing on students’ thinking processes and emerging error patterns. The findings reveal that students encounter various epistemological obstacles across all PISA competency levels (1b to 6), such as conceptual misconceptions, procedural errors, and difficulties in translating contextual information. At the lower levels (1b–3), students struggled to formulate basic algebraic models and perform arithmetic operations. At the higher levels (4–6), they experienced challenges in handling complex calculations, verifying solutions, and applying reasoning in abstract or multi-step situations. These obstacles stem from fragmented prior knowledge, limited exposure to contextual problems, and a lack of reflective habits. This study highlights the importance of integrating authentic real-world problems, providing systematic scaffolding, and fostering continuous self-verification practices in instructional design. The findings offer practical insights for developing targeted pedagogical interventions to enhance students' mathematical literacy and better prepare them to tackle SLETV problems in contexts similar to those featured in PISA.